The Effects of Employee Relations, Workplace Well-Being, and Compensation on Turnover Intentions: The Mediation Role of Work Stress - Yuliantini, Tine; Rahmat, Abdul; Marlapa, Eri; Malihah, Fadhila Dhia; Endri (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: An employee who works at a company may intend to resign from his job for various reasons. Employee Turnover Intention (TI) occurs because it is related to career commitment and the expected utility of the current job in achieving valuable career outcomes. Purpose: This study aims to determine the impact of work relationships, workplace welfare, and compensation on TI mediated by work stress.Design/methodology/approach: PT PICID MM Bogor was used as the research object, and as many as 135 factory employees were respondents. The analysis technique used for hypothesis testing is the Structural Equation Model (SEM)-Partial Least Square (PLS).Findings/Result: The research found that work relationships positively affected work stress, while TI did not. Workplace well-being does not affect work stress, while TI has a positive impact. Compensation has a positive effect on TI and work stress. Job stress directly influences TI and indirectly mediates the influence of employee relations and compensation on TI.Conclusion: Employee relations have a positive impact on work stress. That is, there is a good employee relationship so that employees have positive perceptions or experience stress towards their work. Employee relations do not affect TI. Employee relations do not cause employees to decide to move to another company. Workplace well-being does not affect work stress. Employees feel well-being but do not experience prolonged negative stress. Workplace well-being has a positive impact on TI. The well-being experienced by employees at work causes work stress and has the potential for employees to experience TI.Originality/value (State of the art): This study considers work stress a mediating variable of work relationship factors, workplace well-being, and compensation about turnover intentions. The findings contribute significantly to developing previous empirical literature on human resource management regarding the relationship between work stress and TI. Keywords: employee turnover intention, job satisfaction, job stress, SEM-PLS